Multiple Conserved Heteroplasmic Sites in tRNA Genes in the Mitochondrial Genomes of Terrestrial Isopods (Oniscidea). Issue 7 (1st July 2015) - Chandler, Christopher H; Badawi, Myriam; Moumen, Bouziane; Grève, Pierre; Cordaux, Richard
Abstract: Mitochondrial genome structure and organization are relatively conserved among metazoans. However, in many isopods, especially the terrestrial isopods (Oniscidea), the mitochondrial genome consists of both ∼14-kb linear monomers and ∼28-kb circular dimers. This unusual organization is associated with an ancient and conserved constitutive heteroplasmic site. This heteroplasmy affects the anticodon of a tRNA gene, allowing this single locus to function as a "dual" tRNA gene for two different amino acids. Here, we further explore the evolution of these unusual mitochondrial genomes by assembling complete mitochondrial sequences for two additional Oniscidean species, Trachelipus rathkei and Cylisticus convexus . Strikingly, we find evidence of two additional heteroplasmic sites that also alter tRNA anticodons, creating additional dual tRNA genes, and that are conserved across both species. These results suggest that the unique linear/circular organization of isopods' mitochondrial genomes may facilitate the evolution of stable mitochondrial heteroplasmies, and, conversely, once such heteroplasmies have evolved, they constrain the multimeric structure of the mitochondrial genome in these species. Finally, we outline some possible future research directions to identify the factors influencing mitochondrial genome evolution in this group.